Clinical and Epidemiological Characteristics of Staphylococcus caprae Infections in Catalonia, Spain - Javier Díez de los Ríos; María Navarro; Judit Serra-Pladevall; Sònia Molinos; Emma Puigoriol; Noemi Párraga-Niño; Glòria Pedemonte-Parramón; Luisa Pedro-Botet; Óscar Mascaró; Esteban Reynaga (Microorganisms)
Staphylococcus caprae is a coagulase-negative staphylococcus commonly associated with animals which can also be a zoonotic human pathogen. To date, there is little data available on S. caprae infections. The aim of this study was to characterize the S. caprae infections identified in two hospitals located, respectively, in rural and urban areas of Catalonia, Spain. In this retrospective, observational study, data were compiled from clinical records of all S. caprae infections diagnosed between January 2010 and December 2023. Over the study period, altogether 31 cases of S. caprae infection were identified, with most (23) of these cases occurring in the second half of the period (2017–2023). The mean age of patients was 58.87 ± 20.65 years, and 58.1% were males. Eight patients had had livestock exposure. The most frequent manifestation of infection was skin and soft subcutaneous tissue infections (10; 32.3%), osteomyelitis (6; 19.4%), and joint prosthetic infections (5; 16.1%). All the strains were susceptible to oxacillin, fluoroquinolones, rifampicin, and trimethoprim–sulfamethoxazole. Twenty-two (71%) of the patients required surgical treatment. Only one patient (3.2%) died, because of aortic prosthetic valve infective endocarditis. Skin and soft tissue infections were the most frequently identified manifestations of S. caprae infection. Over 75% of the cases occurred in the last six years, and 25.8% involved significant exposure to livestock. Ongoing surveillance is necessary to better understand the prevalence and transmission dynamics of this emerging zoonotic pathogen.